The Role of Perceived Organization Support Moderation in the Relationship Between Distributive Justice and Procedural Justice on Organizational Citizenship Behavior - Zen, Lucky Muhammad Fuad; Supriadi, Yudi Nur (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of distributive justice and procedural justice on organizational citizenship behavior (OCB) with perceived organizational support (POS) as a moderator variable in private school teachers in Gunung Putri District, Bogor Regency. This study uses a quantitative approach with a survey method of 229 respondents, which was analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4. The results of the study show that distributive justice, procedural justice, and POS have a significant positive effect on OCB. Among the variables of organizational justice, procedural justice has the most dominant influence. Furthermore, POS has been proven to moderate the relationship between procedural justice and OCB, but it is not significant in moderating the relationship between distributive justice and OCB. These findings confirm that organizational support plays an important role in strengthening teachers' perceptions of procedural fairness, thereby encouraging them to behave beyond their formal roles. The novelty of this study lies in the placement of POS as a moderator variable in the relationship between organizational justice and OCB, especially in the private education sector in Indonesia, which has received less attention in the literature. Theoretically, this study expands the understanding of the conditional factors that affect OCB. Practically, the results provide direction for private school managers to create a fair and supportive organizational climate to increase the positive contribution of teachers.